2015
DOI: 10.2355/isijinternational.55.428
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Low Grade Iron Ore (FeOOH) and Biomass Through Integrated Pyrolysis-tar Decomposition (CVI process) in Ironmaking Industry: Exergy Analysis and its Application

Abstract: Effective utilization of low grade iron ore (FeOOH) and biomass represents a promising method to reduce the dependency on fossil fuels and decrease raw material costs in the ironmaking industry. A process system diagram was made and a comparison of exergy losses in conventional methods was conducted to evaluate the proposed system, integrated pyrolysis-tar decomposition over a porous ore through Chemical Vapor Infiltration (CVI) process. As the main product, the CVI ore was employed for energy storage based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…The CVI method directs the formation of nanoscale distances between carbon-iron ore, which causes the reduction rate to occur faster [12]. Investigation of Cahyono et al [13] showed that using the CVI method in a sinter plant could significantly decrease coke breeze and CO 2 emissions in the ironmaking sector. Another study indicated that the reduction rate of composites with the CVI method was higher than that of a mixture of dehydrated iron ore and coke [14].…”
Section: Introductionmentioning
confidence: 99%
“…The CVI method directs the formation of nanoscale distances between carbon-iron ore, which causes the reduction rate to occur faster [12]. Investigation of Cahyono et al [13] showed that using the CVI method in a sinter plant could significantly decrease coke breeze and CO 2 emissions in the ironmaking sector. Another study indicated that the reduction rate of composites with the CVI method was higher than that of a mixture of dehydrated iron ore and coke [14].…”
Section: Introductionmentioning
confidence: 99%
“…Global crude steel production rose by 3.9% from 1.71 Gt in 2018 to 1.78 Gt in 2019, and continued growth is projected in the years to come . The iron and steel industry is, however, one of the most energy-intensive industrial sectors. CO 2 emissions from this industry amounted to approximately 2.0 Gt in 2019, accounting for 24% of the total amount emitted directly from industries . The majority of CO 2 is generated in the iron-making process, which generally employs a blast furnace (BF).…”
Section: Introductionmentioning
confidence: 99%
“…Extensive R&D efforts have been invested in alternative approaches to iron-making from the iron ore, which are largely classified into two types: direct reduction (DR) and smelting reduction processes. , In DR, the iron oxides in iron ore are reduced using reducing gas (H 2 and CO) produced from natural gas or coal in reactors such as shaft furnaces and fluidized bed reactors. The reduction occurs at temperatures below the melting point of iron, producing so-called direct reduced iron or sponge iron.…”
Section: Introductionmentioning
confidence: 99%
“…Exergy is one of the thermodynamic concepts which is able to examine process efficiency in a more comprehensive way [16]. Performing exergy analysis on similar process will be useful to justify the most energy efficient process configuration.…”
Section: Introductionmentioning
confidence: 99%